Highly efficient Cs-based perovskite light-emitting diodes enabled by energy funnelling - Ng, Yan Fong (2020)
The incorporation of phenylethylammonium bromide (PEABr) into a fully inorganic CsPbBr3 perovskite framework led to the formation of mixed-dimensional perovskites, which enhanced the photoluminescence due to efficient energy funnelling and morphological improvements. With a PEABr : CsPbBr3 ratio of 0.8 : 1, PeLEDs with a current efficiency of 6.16 cd A−1 and an EQE value of 1.97% have been achieved.